The Peutinger Map: Carolingian Contents Connected to the Treaty of Aachen - Turković, Tin (2012)
The present knowledge of Early Medieval geographical knowledge is limited, at best. The kind of map Pax Nicephori was negotiated over is undoubtedly an interesting question. Only a handful of scholars have turned their attention to this problem and this line of investigation line is still mostly unexplored. It seems, however, that the usual perception of the Early Medieval geographical knowledge, and the cartography as one of its clearest manifestations, is far from correct. Scholars like N. Lozovsky, B. S. Bachrach, and others have clearly demonstrated that the Early Middle Ages were immeasurably better informed than is usually imagined. Just like today, geographical information was of primary interest for a warring party – Frankish or Byzantine alike. Generally, early medieval cartography is depicted in terms of the so-called Beatus group of maps and the T-type maps. In contrast, late medieval cartography is different, although it stems from the same cartographic roots. One map is distinctly different from all of these medieval maps in content and shape. The so-called Peutinger’s map (Codex Vindobonensis 324), although a panoramic, chorographic map, has many features which are strikingly different from all other medieval maps. The cartographic language employed on the map, as well as the sheer structure of the map, are unmistakably of late Classical (and consequently antique) origin. The pictorial language, manifested in various symbols, can only be compared with that of the early medieval copies of Notitia Dignitatum and Corpus agrimensorum romanorum. The structure and content are clearly compatible with the specific nature of early medieval interests in geography and at the same time are clearly incompatible with the religious- didactic preoccupation of late medieval cartographers. The majority of researchers have assumed that it was produced in the early medieval and not late medieval period... In fact, the only three figural depictions found on the map, representing the cities of Rome, Constantinople, and Antioch, when studied thoroughly, indeed provide a definite clue to the date when the content of the map was produced. In my opinion the content is distinctly early medieval, although many later additions are clearly recognizable. The name by which Jerusalem is labelled (in this case Helya Capitolina), the way in which Salzburg is marked, and other features are facts pointing to the early medieval provenance of the map’s content. All of this information, in fact, suggests an even more precise date – beginning of the 9th century, thus the time of Pax Nicephori. It also illustrates the scope of Carolingian aspirations on the Eastern Adriatic shore, as will be demonstrated in the presentation.
ENG